2013
DOI: 10.1152/ajpcell.00008.2013
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of core clock gene Bmal1 attenuates expression of progesterone and prostaglandin biosynthesis-related genes in rat luteinizing granulosa cells

Abstract: Ovarian circadian oscillators have been implicated in the reproductive processes of mammals. However, there are few reports regarding the detection of ovarian clock-controlled genes (CCGs). The present study was designed to unravel the mechanisms through which CCG ovarian circadian oscillators regulate fertility, primarily using quantitative RT-PCR and RNA interference against Bmal1 in rat granulosa cells. Mature granulosa cells were prepared from mouse Per2-destabilized luciferase (dLuc) reporter gene transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 56 publications
(82 reference statements)
6
52
0
Order By: Relevance
“…Bmal1 control of Ptgs2 transcription has been suggested in other tissues (7,22,25,38). Moreover, our previous data obtained from a DNA microarray in UESCs isolated from day 4.5 of rat pregnancy (49) suggested that the expression level of the Ptgs2 transcript is rhythmic.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Bmal1 control of Ptgs2 transcription has been suggested in other tissues (7,22,25,38). Moreover, our previous data obtained from a DNA microarray in UESCs isolated from day 4.5 of rat pregnancy (49) suggested that the expression level of the Ptgs2 transcript is rhythmic.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study showed that the Ptgs2 protein is gradually expressed in the rat endometrium in response to deciduogenic stimuli (14). More recently, several reports have indicated that the transcription of the Ptgs2 gene is controlled by the cellular circadian clock (7,22,25,56).A growing number of studies have provided evidence that numerous peripheral circadian clock systems are partially selfoperative and independent in their responses to external and internal stimuli other than the stimuli originating from the suprachiasmatic nucleus, known as the central pacemaker of the circadian clock (17,30,55). Circadian clock systems generate cellular rhythms in physiological functions via identified transcriptional and posttranscriptional regulatory processes, which comprise a core group of clock genes and their protein products.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cultured UESCs were first plated in 35-mm collagen-coated dishes with 2 ml of DMEM/F12 supplemented with 1ϫ AA, 1ϫ ITS, and 0.1% BSA. After 24 h in culture, the medium was removed, and the Bmal1 siRNA and nonsilencing RNA diluted in Opti-MEM was transfected into cells using Lipofectamine RNAiMAX reagent (Life Technologies), according to the manufacturer's protocol (12). Both the Bmal1 siRNA and nonsilencing RNA were used at a final concentration of 25 nM.…”
Section: Methodsmentioning
confidence: 99%
“…40,55 For example, Bmal1 knockdown in rat granulosa cells causes, in addition to the downregulation of core clock gene expression (Per1, Per2, Rev-erbα), the disruption of the circadian expression of several ovarian genes, including the LH receptor gene Lhcgr. 56 Similarly, it is plausible, but to date not fully proven, that a circadian clock system also controls the rhythmic expression of clock genes in the theca cells in the ovary. 40 Similarly to the ovaries, a rhythmic expression of cir cadian clock genes, possibly maintained through ovarian signals, 28 is evident in the uterus.…”
mentioning
confidence: 99%